ISCHEMIC PRECONDITIONING AND ITS CARDIOPROTECTIVE EFFECT IN POST-INTERVENTION CARDIAC REHABILITATION PROGRAMMES FOR PATIENTS WITH CORONARY HEART DISEASE - E. S. Karpova; E. V. Kotelnikova; N. P. Lyamina (Российский кардиологический журнал)
In patients with coronary heart disease (CHD), ischemic preconditioning facilitates the mechanisms of cardioprotection and metabolic adaptation to non-fatal ischemia, which is particularly important for the individuals with reduced coronary flow reserve. Development of new cardiac rehabilitation programmes, based on the phenomenon of ischemic preconditioning, is a promising non-pharmacological method of CHD management.